Novel methods for the assessment of chromium species bioavailability - Hamilton, Elliott (2020)
Chromium (Cr) exists in the environment as two chemical species with very different physiological effects. The World Health Organization classifies hexavalent chromium (CrVI) as a carcinogen, whilst trivalent chromium (CrIII) is essential for the regulation of glucose and lipid metabolism. Assessing the risk to human health from CrVI is partly dependent on a greater understanding of the species interconversions at the soil-to-plant interface. Vital to this objective is the validation of techniques capable of accurately determining CrVI in solid matrices such as soil and plant tissues. This thesis aimed to develop, optimise and apply novel analytical methods to understand Cr species interconversions occurring at spatial and temporal scales relevant to plant uptake of Cr from soil. Initially, a modified speciated isotope dilution mass spectrometry (SIDMS) technique, incorporating microwave-assisted alkaline extraction and online species separation, was used to measure CrVI in agricultural soils exposed to elevated metal concentrations through dispersed mine tailings. The CrVI concentrations in all samples indicated a low exposure risk despite optimal conditions for preservation of Cr as the hexavalent species in the tailings material, highlighting the influence of soil characteristics on reduction of CrVI. The mechanisms of Cr species uptake into spinach plants, and the species interconversions occurring prior to uptake, were assessed on a solution basis using isotopic tracers. The impact of sulphate, reported to compete with CrVI for active uptake, was also investigated. The results showed that CrIII could be absorbed from solution into roots through active (symplastic) and passive (apoplastic) mechanisms, with reduction of CrVI observed both after uptake and in the tracer solutions. Sulphate promoted active uptake of CrVI, which was present in the symplast as CrIII. These findings suggested that plants can tolerate CrVI through reduction processes before and after uptake, with evidence of a synergistic effect in the presence of sulphur. The suitability of microdialysis for extracting CrVI from soil solution was appraised during the development of an online system, coupled to HPLC-ICP-QQQ. The setup was able to monitor changes in the concentration of labelled-53CrVI, added to soil through direct spiking and homogenised mixing, at 15-minute intervals, far surpassing the temporal resolution of previous passive sampling techniques. Analytical figures of merit show that the system was sufficiently sensitive (LOD ≤ 0.3 µg L 1) and produced repeatable measurements (RSD of standards < 2.5%), demonstrating that it is a powerful tool for providing further insight into the bioavailability of CrVI and its interactions with soil microbes and the rhizosphere. This thesis contributes to a better understanding of plant-Cr species dynamics, and demonstrates the importance of developing and validating accurate, high-resolution analytical techniques to investigate existing and emerging research questions surrounding soil-to-plant transfer of CrVI.